Asparaginase activity levels and monitoring in patients with acute lymphoblastic leukemia. Issue 8 (3rd August 2018) - Salzer, Wanda; Bostrom, Bruce; Messinger, Yoav; Perissinotti, Anthony J.; Marini, Bernard
Abstract: Asparaginase is an integral component of multiagent chemotherapy regimens for the treatment of acute lymphoblastic leukemia (ALL). Adequate asparagine depletion is believed to be an important factor in achieving optimal therapeutic outcomes. Measurement of asparaginase activity allows practitioners to evaluate the potential effectiveness of therapy in real time. Asparaginase activity levels can be used to identify patients with silent inactivation and modify therapy in these patients. Patients with silent inactivation to asparaginase who are switched to therapy with an immunologically distinct asparaginase exhibit outcomes similar to patients who never developed silent inactivation. Despite these benefits, there exists no universally agreed-upon guideline for treatment adjustments based on asparaginase activity levels. The goal of this manuscript is to review the clinical evidence linking asparaginase activity levels to outcomes in patients with ALL and to provide an overview of how asparaginase activity levels may be used to guide treatment.